SDGs and Business Ethics in Islamic Financing: Balancing Profit and Sharia Compliance - Mathayo Marko Nassari; Muhammad Abuzar (Walidem Institute and Publishing (WIP), 2025)
Objective: This study examines how Islamic financial institutions balance profitability and sharia compliance in murabahah transactions while contributing to the achievement of the Sustainable Development Goals (SDGs), particularly SDG 8 (Decent Work and Economic Growth), SDG 10 (Reduced Inequalities), SDG 12 (Responsible Consumption and Production), and SDG 16 (Peace, Justice, and Strong Institutions). The research aims to identify effective ethical strategies that enable Islamic financial institutions to maintain competitive financial performance without compromising adherence to Islamic principles. Theoretical framework: The study is grounded in Islamic business ethics theory, stakeholder theory, and the maqāṣid al-sharī‘ah framework, which collectively emphasize justice, transparency, accountability, and social welfare in financial transactions. Literature review: A review of the existing literature indicates that although murabahah remains the dominant financing instrument in Islamic finance, concerns persist regarding excessive profit orientation, weak compliance mechanisms, and the limited integration of sustainability objectives into financing practices. Methods: This research employs a qualitative case study approach. Data were collected through in-depth interviews with senior managers, sharia supervisory personnel, and experienced practitioners in the Islamic financial industry. The data were analyzed using thematic analysis to identify recurring patterns, challenges, and strategic responses associated with the profit–compliance dilemma in murabahah transactions. Results: The findings reveal that Islamic financial institutions face significant challenges in balancing market competitiveness with strict sharia adherence. Nevertheless, several effective strategies were identified, including strengthening employees’ understanding of sharia principles, developing products aligned with Islamic ethical values, enhancing internal supervision and compliance monitoring, and fostering trust-based relationships with customers through transparency and fairness. These strategies not only support sustainable profitability but also reinforce institutional contributions to inclusive economic growth, ethical consumption, and good governance as promoted by the SDGs. Implications: The study implies that integrating Islamic business ethics with sustainability objectives can strengthen the long-term resilience and legitimacy of Islamic financial institutions. Novelty: Its novelty lies in linking the profit–compliance dilemma in murabahah transactions with the SDG framework, offering a comprehensive ethical-sustainability perspective that has received limited attention in previous studies.